Effectiveness of Physics Learning with PBL Model Assisted by 3D Webbook Integrated with Environmental Learning in Improving Students' Critical Thinking Skills - Zahro, Fithriatiz; Lestari, Nurita Apridiana; Sya’roni, Imam (JPPS (Jurnal Penelitian Pendidikan Sains), 2025)
Objective: This study aims to examine the effectiveness of applying the Problem Based Learning (PBL) model assisted by 3D Webbook integrated with Environmental Learning in improving students' critical thinking skills on global warming material. Method: This study used a pre-experiment method with a One-Group Pretest-Posttest design. The research subjects consisted of two classes (X-1 and X-2), each comprising 36 students, selected through purposive sampling technique. The instruments used included a critical thinking skills test in the form of descriptive questions and an observation sheet to assess the implementation of learning syntax. The validity of the device was assessed by experts using a five-point scale and the reliability test was carried out using SPSS with the Cronbach's Alpha formula. Results: (1) The average pretest scores of classes X-1 and X-2 were 35.61 and 33.11, respectively, increasing to 85.11 and 83.78 on the posttest.  (2) N-gain scores in both classes were categorized as high.  (3) Syntax implementation reached an average of 93%. Novelty: This research introduces an innovation by integrating the PBL model with digital technology through a 3D Webbook combined with Environmental Learning. This integration enables flexible access to materials without requiring large file downloads and contextualizes relevant environmental issues to support the development of 21st-century critical thinking skills.